The use of phylogenetic reconstruction as a predictive tool to functionally identify raffinose family oligosaccharide (RFO) producing glycosyltransferases - Jansen van Rensburg, Thomas (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScAgric)--Stellenbosch University, 2022.